The sacred significance of Thracian and Dacian domestic altars decorated with ornaments - Makiewicz, Tadeusz (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of the interpretation of the function and meaning of ornamented clay altars discovered in the area of Thrace and Dacia. The problem is significant because these objects constitute part of a broader cultural phenomenon in Europe, and their function was not clearly defined. The aim of the work is to determine their sacred character and their place in the system of beliefs. The author applies archaeological analysis including form, ornamentation, context of occurrence, and accompanying finds. The most important results indicate that the altars occurred both in houses and in buildings of a special character as well as in barrows, and their ornamentation shows regional differentiation, with Dacian objects being simpler than Thracian ones. The analysis has shown that they were connected with domestic cults, probably of protective deities, and that their function could extend to the level of the tribal community. It has also been pointed out that there is developmental continuity of this type of object and transformations leading to the separation of cult spaces outside the house. The conclusion is that ornamented altars constituted an important element of domestic religion, which over time underwent institutionalization and expansion of social functions.